2014
DOI: 10.1002/2013jd020854
|View full text |Cite
|
Sign up to set email alerts
|

On the percentage of lightning flashes that begin with initial breakdown pulses

Abstract: The initial breakdown (IB) stage of lightning flashes typically occurs in the first 20 ms of a flash and includes a series of IB pulses often detected with electric field change sensors. There is disagreement about the percentage of negative cloud-to-ground (CG) flashes that begin with IB pulses. This study includes new data on IB pulses in 198 CG flashes in Austria (latitude~48˚N), Florida, USA (~29˚N) and South Dakota, USA (~44˚N) with, respectively, 100%, 100%, and 95% of the flashes having IB pulses. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
115
3
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(136 citation statements)
references
References 33 publications
17
115
3
1
Order By: Relevance
“…It is statistically significant at the 99.9% confidence level. Similar trends were previously observed in Florida [12], Japan [25], and China [26]. …”
Section: Characteristics Of Pb Pulse Trainssupporting
confidence: 89%
See 1 more Smart Citation
“…It is statistically significant at the 99.9% confidence level. Similar trends were previously observed in Florida [12], Japan [25], and China [26]. …”
Section: Characteristics Of Pb Pulse Trainssupporting
confidence: 89%
“…Statistics for the PB-RS interval, PB/RS pulse peak ratio, PB pulse train duration, and bipolar pulse width, as well as for the NLDN-reported current and distance are given in Table 1. The AM PB/RS pulse peak ratio of 0.15 in Table 1 is comparable to the AM values of 0.20 to 0.29 reported in [8,12,17]. The AM PB-RS interval of 8.8 ms in Table 1 is more than a factor of two smaller than previously reported, this disparity being likely due to the very high AM peak current of 134 kA (GM = 122 kA) in our dataset.…”
Section: Characteristics Of Pb Pulse Trainssupporting
confidence: 82%
“…Higher latitudes have a higher percentage of detectable PBPs than lower latitudes. In contrast, many researchers have argued that the first return stroke always involves PBPs in all negative CG flashes [7][8][9]. Their studies revealed that the detectable PBP percentage does not depend on latitude.…”
Section: Introductionmentioning
confidence: 94%
“…These pulses are called initial breakdown pulses or IBPs herein and have been called preliminary breakdown pulses, B pulses, and characteristic pulses by others. Many studies have been carried out using E-change sensors to characterize IBPs and to understand the physics behind them [e.g., Appleton and Chapman, 1937;Clarence and Malan, 1957;Kitagawa and Brook, 1960;Weidman and Krider, 1979;Beasley et al, 1982;Gomes et al, 1998;Nag and Rakov, 2008;Nag et al, 2009;Marshall et al, 2014]. Most of these studies have focused on the largest amplitude IBPs, which have a typical duration of 10-100 μs and often have several fast-rising subpulse on the initial portion of the bipolar waveform [e.g., Weidman and Krider, 1979]; these pulses have been called "classic" IBPs by Nag et al [2009].…”
Section: Introductionmentioning
confidence: 99%